Biomimetic pangolin-scale sustainable cellulose-based composite paper serves as a multifunctional platform for portable radiative cooling - Fengqiong Jiang; Yuancheng Zhang; Zhen Wang; Tao Zheng; Yuntong Liang; Chuanhui Xu; Bai Huang; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2026)

Intelligent recognition of the fermentation stage of baijiu based on multi-dimensional data fusion and interpretable machine learning - Lin Du; Junchao Zhou; Yongqing Tang; Xuan Liu; Jing Zhong; Bo Yang; Yuancheng He; Xianguo Tuo; Haiping Du (Food Research International, 2026)

Scalable production of antioxidant ‘sandwich’ films from all-natural composites for inhibiting fruit browning - Jie Deng; Hao Fu; Xinhong Li; Jieping Liu; Yuancheng Zhang; Wenxin Zhao; Baofeng Lin (Food Chemistry, 2026)

Social Network and Value Chain Integration: Unraveling the Formation and Evolution of Meizhou Pomelo Industry Cluster in China - Ren Yang; Yuancheng Lin; Xin Zhang (Chinese Geographical Science, 2026)

Active cellulose-based film with synergistic enhanced photothermal antibacterial effects by Fe-doped ZIF-8 and EGCG for efficient litchi preservation - Wenxin Zhao; Yuntong Liang; Yuancheng Zhang; Yongfu Deng; Hao Fu; Xu Yuan; Zhen Wang; Xiaohe Lu; Baofeng Lin (Chemical Engineering Journal, 2025)

Filament-woven SF/PA gel for removing ultrafine nanoparticles and unmanageable hazardous pollutants by "all-in-one net" - Qiumei Wei; Yuancheng Zhang; Fengqiong Jiang; Lihua Fu; Bai Huang; Chuanhui Xu; Baofeng Lin (Journal of Environmental Management, 2025)

Short-term coalbed methane concentration prediction and early warning based on the STL-ENN-GRU hybrid model - Kangle Li; Lin Jiang; Yan Zhang; Mei Wang; Yuancheng Li; Kun Yang (Earth Science Informatics, 2025)

Flexible fiber composite functional materials based on Fe-MOFs nanozyme catalytic activity for efficient point-of-use water disinfection - Hao Fu; Hao Li; Qiuwen He; Guangwu Du; Jianfang Li; Yuancheng Zhang; Yuntong Liang; Baofeng Lin (Chemical Engineering Journal, 2024)

Production and reconstruction mechanism of consumption spaces in urban fringe areas under capital intervention: Evidence from Guangming town in Shenzhen - Yuancheng Lin; Ren Yang (Journal of Rural Studies, 2024)

A preliminary assessment of CO2 capture, transport, and storage network for China's steel sector - Yuancheng Lin; Tubagus Aryandi Gunawan; Cecelia Isaac; Hongxi Luo; Fangwei Cheng; Eric D. Larson; Chris Greig; Linwei Ma; Zheng Li (Journal of Cleaner Production, 2024)

Coordinating energy and material efficiency strategies for decarbonizing China's iron and steel sector - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Understanding the drivers of CO2 growth in China's iron and steel sector: An integrated analysis of the energy–material–economy nexus - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

How will China's steel demand develop under the investment-driven patterns? Integrating extended input-output model with dynamic steel flow analysis - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Rural Development Transformation and Social Governance from the Perspective of Specialization: A Case Study of Ruiling Village in Guangzhou City, China - Yuancheng Lin; Ren Yang; Simeng Li (Chinese Geographical Science, 2023)

Enhanced antibacterial effect and biodegradation of coating via dual-in-situ growth based on carboxymethyl cellulose - Zhenhao Lin; Hao Fu; Yuancheng Zhang; Yongfu Deng; Fuxiang Wei; Hao Li; Chuanhui Xu; Fuli Hua; Baofeng Lin (Carbohydrate Polymers, 2023)

Hybridization of carboxymethyl chitosan with bimetallic MOFs to construct renewable metal ion “warehouses” with rapid sterilization and long-term antibacterial effects - Hao Li; Yuwei Zhang; Yuancheng Zhang; Fuxiang Wei; Yongfu Deng; Zhenhao Lin; Chuanhui Xu; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2023)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

A Novel Fluorescent Nanoparticle for Sensitive Detection of Cry1Ab Protein In Vitro and In Vivo - Xiao Xu; Hao Chen; Yuancheng Cao; Yongjun Lin; Jun’an Liu (Journal of Fluorescence, 2018)

Three-dimensional shallow velocity structure beneath Taal Volcano, Philippines - Shuei-Huei You; Konstantinos I. Konstantinou; Yuancheng Gung; Cheng-Horng Lin (Journal of Seismology, 2017)

Remobilizing deleted piggyBac vector post-integration for transgene stability in silkworm - Feng Wang; Riyuan Wang; Yuancheng Wang; Hanfu Xu; Lin Yuan; Huan Ding; Sanyuan Ma; You Zhou; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2015)

Overexpression of recombinant infectious bursal disease virus (IBDV) capsid protein VP2 in the middle silk gland of transgenic silkworm - Hanfu Xu; Lin Yuan; Feng Wang; Yuancheng Wang; Riyuan Wang; Chunnuan Song; Qingyou Xia; Ping Zhao (Transgenic Research, 2014)

Overexpression and functional characterization of an Aspergillus niger phytase in the fat body of transgenic silkworm, Bombyx mori - Hanfu Xu; Yaowen Liu; Feng Wang; Lin Yuan; Yuancheng Wang; Sanyuan Ma; Helen Beneš; QingYou Xia (Transgenic Research, 2014)

An optimized sericin-1 expression system for mass-producing recombinant proteins in the middle silk glands of transgenic silkworms - Feng Wang; Hanfu Xu; Lin Yuan; Sanyuan Ma; Yuancheng Wang; Xiaoli Duan; Jianping Duan; Zhonghuai Xiang; Qingyou Xia (Transgenic Research, 2013)